Geographic differences in community oncology provider and practice location characteristics in the central United States. Issue 4 (5th April 2022) - Ellis, Shellie D.; Thompson, Jeffrey A.; Boyd, Samuel S.; Roberts, Andrew W.; Charlton, Mary; Brooks, Joanna Veazey; Birken, Sarah A.; Wulff‐Burchfield, Elizabeth; Amponsah, Jonah; Petersen, Shariska; Kinney, Anita Y.; Ellerbeck, Edward
Abstract: Purpose: How care delivery influences urban‐rural disparities in cancer outcomes is unclear. We sought to understand community oncologists' practice settings to inform cancer care delivery interventions. Methods: We conducted secondary analysis of a national dataset of providers billing Medicare from June 1, 2019 to May 31, 2020 in 13 states in the central United States. We used Kruskal‐Wallis rank and Fisher's exact tests to compare physician characteristics and practice settings among rural and urban community oncologists. Findings: We identified 1, 963 oncologists practicing in 1, 492 community locations; 67.5% practiced in exclusively urban locations, 11.3% in exclusively rural locations, and 21.1% in both rural and urban locations. Rural‐only, urban‐only, and urban‐rural spanning oncologists practice in an average of 1.6, 2.4, and 5.1 different locations, respectively. A higher proportion of rural community sites were solo practices (11.7% vs 4.0%, P <.001) or single specialty practices (16.4% vs 9.4%, P <.001); and had less diversity in training environments (86.5% vs 67.8% with <2 medical schools represented, P <.001) than urban community sites. Rural multispecialty group sites were less likely to include other cancer specialists. Conclusions: We identified 2 potentially distinct styles of care delivery in rural communities, which may require distinct interventions: (1) innovation‐isolated rural oncologists, who are more likely to be solo providers, provide care at few locations, and practice with doctors with similar training experiences; and (2) urban‐rural spanning oncologists who provide care at a high number of locations and have potential to spread innovation, but may face high complexity and limited opportunity for care standardization.